Pseudacanthicus major: description of one of the largest known Loricariidae (Hypostominae: Ancistrini), a species from rio Tocantins basin, Brazil - Chamon, Carine C.; Silva, Thiago Costa E (Zootaxa, 2018)
The genus Pseudacanthicus currently comprises the following six species distributed in the Amazon and Tocantins basins, and coastal drainages from Guyana to French Guyana: P. serratus, P. fordii, P. histrix, P. spinosus, P. leopardus, P. pitanga, and P. pirarara. Herein we describe P. major, from rio Tocantins basin, one of the largest loricariid species known. The new species is distinguished from its congeners by the following combination of characters: having body color pattern with dark brown background without spots or blotches and dorsal and caudal fins with transversal white bands; anterior process of compound pterotic with no contacting with the posterior margin of the orbit and by the absence of a conspicuous crest on the posterior edge of parieto-supraocciptal. Other osteological characteristics are further used to diagnose P. major from others congeners. A discussion on gigantism and miniaturization in freshwater fish, ornamental fisheries activities, threats and conservation of the new species are also provided.